The Handbook of person-centered psychotherapy and counselling - Cooper, Mick (Chartered counselling psychologist).; Malta, Gina di; O'Hara, Maureen Miller; Gololob, Yana; Stephen, Susan (London : Bloomsbury Academic, 2024)
"Thoroughly updated to reflect the latest trends in theory ad practice, this third edition is the most in-depth and wide-ranging text available n person-centered psychotherapy and counselling. Written by a diverse range of expert contributors, this is a cutting-edge resource for students of psychotherapy and counselling on a range of programs as well as professional practitioners working in the field.
Includes bibliographical references and index.
Keywords: Client-centered psychotherapy